2018
DOI: 10.31382/eqol.190604
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inertial resistance squat exercise protocol based on novel exercise intensity determination on physical fitness of older adult women

Abstract: <p>The aim of the study was to examine practical implications and actual effects of the 8-week progressive resistance exercise protocol with the custom-made inertial device on sit-to-stand, 6- MWT, functional reach, up-and-go test results and Rate of Perceived exertion (RPE) among older adult women (age 65-74). Thirty-seven healthy volunteers were randomly assigned to the control group (n = 11) and to two exercise – inertial (n = 12) and traditional (n = 14) – groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The highest number of participants was 45 [25], while the lowest was 12 [26][27][28]. A female sample of participants only was found in two studies [25,31], a male sample was found in two studies as well [27,28], while the rest of the five studies had a mixed gender sample [24,26,29,30,32]. The participants were healthy in most of the included studies, and the physically active were found in five studies [25,[27][28][29]32], except the case of Fernandez-Gonzalo et al [26], where the sample consisted of chronic stroke patients.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…The highest number of participants was 45 [25], while the lowest was 12 [26][27][28]. A female sample of participants only was found in two studies [25,31], a male sample was found in two studies as well [27,28], while the rest of the five studies had a mixed gender sample [24,26,29,30,32]. The participants were healthy in most of the included studies, and the physically active were found in five studies [25,[27][28][29]32], except the case of Fernandez-Gonzalo et al [26], where the sample consisted of chronic stroke patients.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 96%
“…The longest experimental program lasted 13 weeks [32], while the shortest was 4 weeks [25]. Trainings per week were not more than three times and not less than two times, and only one study did not show that information [31]. The sets varied from 1 to 4, and the repetition within also varied from 7 to 22 or from 2 to 7 repetitions maximum.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…As eccentric muscle strength declines with age to a lesser degree than other types of muscle strength, it may represent an effective stimulus for adaptation in older adults, playing a key role in successful ageing [ 49 , 50 , 51 ]. In particular, isoinertial resistance exercise has been suggested as a potential training modality in certain aging populations ready for higher resistance exercise stress [ 52 , 53 ], with studies mainly focusing on knee extension [ 53 , 54 , 55 ] and squat [ 56 , 57 ] exercises.…”
Section: The Undiscovered Benefits Of Isoinertial Resistance Trainmentioning
confidence: 99%
“…Flywheel knee extension trainings (8–12 weeks; 3 times/week; 7–12 repetitions; 1–4 sets per session) elicited beneficial modifications in muscle mass, strength, and architecture, and improved the quality of life and functional performances in 68-year old men [ 53 , 55 ] and the peak knee extension power in 70-year old men and women [ 54 ]. Isoinertial squat trainings (6–8 weeks; 2–3 times/week; 9–15 repetitions; 2–4 sets per session) improved mobility, balance, mean concentric propulsive velocity, and power in 65-year old men and women [ 57 ], as well as physical and functional abilities in 68-year old women [ 56 ]. While strength-related gains could be expected after isoinertial resistance trainings, improvements in functional abilities, specifically balance, are quite intriguing.…”
Section: The Undiscovered Benefits Of Isoinertial Resistance Trainmentioning
confidence: 99%
See 1 more Smart Citation